Teaching Factory-Based Field Work Practice Learning Model to Improve Vocational High School Students' Competencies - Masliha Masliha; Mustofa Kamil; Luluk Asmawati (Jurnal Pendidikan Abad Ke-21, 2026)
This research aimed to develop a valid and practical Teaching Factory-based Field Work Practice learning model to improve the competency of Vocational High School students. This research is motivated by the suboptimal implementation of Field Work Practice, which is still lacking in structure, measurement, and is not fully aligned with industry standards. This research used a Research and Development (RD) approach with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The research instruments consisted of an expert validation sheet and a teacher practicality questionnaire with a five-level scale. The validation subjects involved five experts, while the practicality test was conducted by five teachers teaching the Field Work Practice subject. The results showed that the TeFa-based Field Work Practice learning model achieved a validity level of 93.15%, categorized as very valid, and a practicality level of 90.8%, categorized as very practical. These results indicate that the developed model has high design quality, is easy to implement, and is relevant to the needs of industry-based learning. The implication of this research is that the Teaching Factory-based Field Work Practice model can be used as a strategic alternative in implementing Field Work Practice in vocational schools, especially in overcoming limited industrial access, as well as contributing to improving student competencies through authentic, structured, and work-oriented learning experiences.